Relation of power, speed and agility in basketball players by position - Stankovic, D.; Tsankova-Kaloyanova, M. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The aim of this study was to determine differences in motor skills among top NBA players. In order to conduct the research, data was collected from the official NBA Draft Combine website, where statistical analysis of information was done in order to determine the differences between players depending on the players' positions. We analyzed the variables that characterize agility and strength, which are integral parts of the battery of tests applied to this draft. Based on "One Way ANOVA", it can be concluded that the arithmetic mean of the applied tests differs significantly in three motor variables at the level of p.0.01 in relation to players playing in different positions (Lane Agility Time, Three Quarter Sprint and Max Vertical Leap). In all these variables, groups of players were formed and homogenized with similar average values in relation to body height that definitely determines the values of the performed motor skill tests, as shown by post-hoc analysis. A group of "lower-height" players (Shooting guard, Small forward and Point guard) showed on all three tests that their arithmetic means do not differ statistically, so their test results are very similar, which quite explains the tendency of modern basketball that on the positions 1-3 players can easily rotate.